Testing business ideas - Bland, David J., 1976-; Osterwalder, Alexander (Hoboken, New Jersey : John Wiley & Sons, Inc., 2020)
'There is a large knowledge gap in the market today between business strategy and experimentation. People resort to reading growth hacker blogs or going to meetups or eventually asking consultants for help. This book contains a library of techniques and specific guidance on how to rapidly test new business ideas in the market with customers, using the world renowned Business Model Canvas. The book has three parts. The first explains how Lean Experiments dramatically reduce risk and increase the likelihood of success for any new business idea. The second part introduces Assumptions Mapping and an experiment library. The third part defines a series of ceremonies and team configurations to make experimentation a continuous, repeatable process. The book concludes with a challenge to founders and executives on how to encourage an experimentation mindset within their organizations'--
Includes index.
Keywords: Strategic planning; Consumer research; New products